2007
DOI: 10.1177/1082013207075655
|View full text |Cite
|
Sign up to set email alerts
|

Note. Speciation of Arsenic in Licorice Confectionery Products and Estimation of Health Risks

Abstract: Total-arsenic (T-As) and arsenic (As) species were determined by HPLC-HG-AAS in ten different confectionery products: nine throat pearls and an industrial licorice extract. The Spanish legislation sets a maximum total-As content in confectionery products at 0.1mg/g. T-As concentrations were above the permitted maximum limit (mean of 0.219±0.008mg/g). All As was present in the form of toxic inorganic species. The daily consumption of licorice-confections in Spain is 1.1g and leads to a daily intake of inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The methodology used for the extraction of the As species was that first described by Heitkemper and others () and later by Signes and others () and Munera‐Picazo and others (, ). 1 g of milled and dried samples was treated with 3 mL of 2 M TFA.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used for the extraction of the As species was that first described by Heitkemper and others () and later by Signes and others () and Munera‐Picazo and others (, ). 1 g of milled and dried samples was treated with 3 mL of 2 M TFA.…”
Section: Methodsmentioning
confidence: 99%
“…They confirmed the predominantly inorganic nature of As in the whole samples by XANES. Signes et al 334 determined As species in ten different Spanish licorice confectionery products. They found total concentrations (0.219 AE 0.008 mg g À1 ) above the permitted maximum limit of 0.1 mg g À1 , but concluded that as the daily consumption of licorice confections in Spain is 1.1 g, the daily intake of inorganic As of 0.23 mg from this source is only 0.2% of the tolerable daily intake of inorganic As for a teenager.…”
Section: Liquid Chromatographymentioning
confidence: 99%